Patterns of Lymph Node Metastasis and Optimal Surgical Strategy in Small (≤20 mm) Gastroenteropancreatic Neuroendocrine Tumors - Cai, Yibo; Liu, Zhuo; Jiang, Lai; Ma, Dening; Zhou, Zhenyuan; Ju, Haixing; Zhu, Yuping (Frontiers in Endocrinology, 2022)
Background: Regional lymph node metastasis (LNM) is crucial for planning additional lymphadenectomy, and is directly correlated with poor prognosis in gastroenteropancreatic neuroendocrine tumors (GEP-NETs). However, the patterns of LNM for small (≤ 20 mm) GEP-NETs remain unclear. This population-based study aimed at evaluating LNM patterns and identifying optimal surgical strategies from the standpoint of lymph node dissemination. Methods: This retrospective cohort study retrieved data from the Surveillance, Epidemiology, and End Results (SEER) 18 registries database for 17308 patients diagnosed as localized well-differentiated GEP-NETs ≤ 20 mm between January 1, 2004, and December 31, 2017. The patterns of LNM were characterized in 6622 patients underwent extended resection for adequate lymph node harvest. Results: Of 6622 patients with localized small GEP-NETs in the current study, 2380 (36%) presented with LNM after regional lymphadenectomy. Nodal involvement was observed in approximately 7.4%, 49.1%, 13.6%, 53.7%, 13.8%, 7.8% and 15.4% of gastric (g-), small intestinal (si-), appendiceal (a-), colonic (c-), rectal (r-), non-functional pancreatic (nfp-) and functional pancreatic (fp-) NETs ≤ 20 mm. Patients with younger age, larger tumor size and muscularis invasion were more likely to present with LNM. Additional lymphadenectomy conferred a significant survival advantage in NETs (≤ 10 mm: HR, 0.47; 95%CI, 0.33-0.66; P < 0.001; 11-20 mm: HR, 0.54; 95%CI, 0.34-0.85; P = 0.008) and fp-NETs ≤ 20 mm (HR, 0.08; 95%CI, 0.02-0.36; P = 0.001), as well as g-NETs (HR, 0.39; 95%CI, 0.16-0.96; P = 0.041) and c-NETs of 11-20 mm (HR, 0.07; 95%CI, 0.01-0.48; P = 0.007). Survival benefits of additional lymphadenectomy were not found in a-NETs, r-NETs, and nfp-NETs with small size. Conclusions: Given the increased risk for nodal metastasis, primary tumor resection with regional lymphadenectomy is a potential optimal surgical strategy for si-NETs and fp-NETs ≤ 20 mm, as well as g-NETs and c-NETs of 11-20 mm. Local resection is an appropriate and reliable surgical approach for a-NETs, r-NETs, and nfp-NETs ≤ 20 mm.